Jum, el indio impensable de La casa verde y de Mario Vargas Llosa - Cabel García, Andrea Elvira (2020)
This article is a postcolonial and post subaltern reading of The Green House (1966), from the Peruvian Nobel Laureate Mario Vargas Llosa. Our aim is to explore and develop two mechanisms of agency of Jum, the aguaruna chief. These mechanisms can be observed in two specific moments: in his battle for the stablishment of a cooperative, and in what we call "body speech". This paper contends that Jum decenter and surprise the storyteller and the characters because he proposes an alternative indigenous representation that overcomes the traditional representation, usually Orientalized of the indigenous people. To demonstrate it, we focus on two theorical concepts: the unthinkable and critical re-reading of "defamiliarization". Our main objective is to demonstrate that Jum embodies a complex paradigm of Amazonian indigeneity that seeks to problematize the violence towards the Amazonian indigenous people.